Analisis IT Service Management (ITSM) Menggunakan Framework ITIL V4 pada Dinas Kependudukan dan Pencatatan Sipil Kota Palembang - Theresia Chintia Herawati; Dicky Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the management of information technology services at the Department of Population and Civil Registration of Palembang City using the Information Technology Service Management (ITSM) approach based on the ITIL V4 framework. The IT services analyzed include the Population Administration Information System (SIAK) and Digital Population Identity (IKD), which support public service delivery. This research employs a descriptive analytical method with a mixed methods approach, combining qualitative and quantitative techniques. Data were collected through literature studies, direct observation, interviews, and questionnaire distribution to relevant stakeholders determined through RACI mapping. Data analysis was conducted using SWOT analysis, fishbone analysis to identify root causes of problems, maturity level measurement, and gap analysis. The research focuses on the Service Management Practices domain of ITIL V4, namely Incident Management, Problem Management, and Service Continuity Management. The results indicate that the maturity level of IT service management in all three practices is at Level 4 (Managed), demonstrating that IT service processes have been implemented effectively and are systematically managed. However, minor gaps remain, particularly in documentation, root cause analysis, procedure standardization, and service continuity planning. Therefore, this study provides improvement recommendations to enhance sustainable IT service management and support the improvement of public service quality.